Red Blood Cell Transfusion Practices in the Neurointensive Care Unit: A Narrative Review - Surve, Rohini M.; Bansal, Sonia; Muthuchellappan, Radhakrishnan (Journal of Neuroanaesthesiology and Critical Care, 2019)
Anemia is common in neurointensive care unit (NICU) patients and is one of the common causes of systemic insults to the brain. Though the recent literature favors restrictive blood transfusion practices over liberal transfusion to correct anemia in the general ICU, whether a similar practice can be adopted in NICU patients is doubtful due to lack of strong evidence. Impairment of cerebral autoregulation and cardiac function following acute brain injury affects the body's compensatory mechanism to anemia and renders the brain susceptible to anemic hypoxia at different hemoglobin (Hb) thresholds. Hence, red blood cell transfusion (RBCT) practice based on a single Hb threshold value might be inappropriate. On the other hand, allogenic RBCT has its own risks, both in short and in long run, leading to adverse outcomes. Thus, instead of relying only on arbitrary Hb values, a better way to decide the need for RBCT in NICU patients is to target parameters based on systemic and regional cerebral oxygenation. This approach will help us to individualize RBCT practices. In this narrative review, based on the available literature, authors have discussed the impact of anemia and blood transfusion on the immediate and late neurological outcomes and the current role of regional brain monitoring in guiding blood transfusion practices. In the end, authors have tried to update on the current RBCT practices in neurosurgical and neuromedical patients admitted to the NICU.
Keywords: red blood cell transfusion; neurointensive care unit; anemia; acute brain injury